2021
DOI: 10.7203/sjp.18.2.21650
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciação das icnoespécies e variantes de Arthrophycus e sua utilização problemática em icnoestratigrafia: o resultado de homoplasias comportamentais entre anelídeos e artrópodes?

Abstract: O icnogénero Arthrophycus Hall, 1852 presente no Arenigiano-Oretaniano da Formação do Quartzito Armoricano (Portugal) é revisto com base em novos dados e na re-avaliação das colecções de Nery Delgado, sendo descritas duas icnoespécies, A. alleghaniensis (Harlan, 1831) e A. linearis Seilacher, 2000, com as variantes morfoetológicas A. alleghaniensis lateralis e A. linearis tipo protrusiva. Os resultados alcançados para Portugal entram em conflito, do ponto de vista estratigráfico, icnotaxonómico e comportamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Upper portions of the Vila Maria Formation are currently dated as Llandovery, initially on the basis of the presence (Burjack and Popp, 1981) of the Cambrian-early Silurian (Neto de Carvalho et al, 2003) ichnospecies Arthrophycus alleghaniensis (Harlan, 1831) (also found in the upper part of the Aldeia Creek section [Adôrno et al, 2016]) and later confirmed by palynomorph assemblages (Gray et al, 1985). Additional radiometric Rb-Sr data from the Três Barras Farm section (Mizusaki et al, 2002) indicate an absolute dating of 435.9 ± 7.8 Ma for the shale levels from the Vila Maria Formation, which places it slightly over, but still into the chronologic range of, the late Hirnantian (443.8 ±1.5 Ma).…”
Section: Discussionmentioning
confidence: 99%
“…Upper portions of the Vila Maria Formation are currently dated as Llandovery, initially on the basis of the presence (Burjack and Popp, 1981) of the Cambrian-early Silurian (Neto de Carvalho et al, 2003) ichnospecies Arthrophycus alleghaniensis (Harlan, 1831) (also found in the upper part of the Aldeia Creek section [Adôrno et al, 2016]) and later confirmed by palynomorph assemblages (Gray et al, 1985). Additional radiometric Rb-Sr data from the Três Barras Farm section (Mizusaki et al, 2002) indicate an absolute dating of 435.9 ± 7.8 Ma for the shale levels from the Vila Maria Formation, which places it slightly over, but still into the chronologic range of, the late Hirnantian (443.8 ±1.5 Ma).…”
Section: Discussionmentioning
confidence: 99%